2021
DOI: 10.1111/febs.16216
|View full text |Cite
|
Sign up to set email alerts
|

Inactive pseudoenzyme subunits in heterotetrameric BbsCD, a novel short‐chain alcohol dehydrogenase involved in anaerobic toluene degradation

Abstract: Anaerobic toluene degradation proceeds by fumarate addition to produce (R)-benzylsuccinate as first intermediate, which is further degraded via β-oxidation by five enzymes encoded in the conserved bbs operon. This study characterizes two enzymes of this pathway, (E)-benzylidenesuccinyl-CoA hydratase (BbsH), and (S,R)-2-(α-hydroxybenzyl)succinyl-CoA dehydrogenase (BbsCD) from Thauera aromatica. BbsH, a member of the enoyl-CoA hydratase family, converts (E)-benzylidenesuccinyl-CoA to 2-(α-hydroxybenzyl)succinyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 100 publications
1
16
0
Order By: Relevance
“…The optimum pH for benzoylsuccinyl-CoA formation from benzoyl-CoA and succinyl-CoA was at pH 6.4, and HPLC analyses confirmed that BbsAB catalyzed the time-dependent decrease of succinyl-CoA and benzoyl-CoA with a simultaneous increase of a new compound, which comigrated with benzoylsuccinyl-CoA obtained in another study (Fig. 2C) [10]. The chemical nature of this product as a ketone-containing compound was further supported by converting it to a hydrazone by adding phenylhydrazine, resulting in a shift of the retention time (Fig.…”
Section: Functional and Molecular Properties Of Bbsabsupporting
confidence: 67%
See 4 more Smart Citations
“…The optimum pH for benzoylsuccinyl-CoA formation from benzoyl-CoA and succinyl-CoA was at pH 6.4, and HPLC analyses confirmed that BbsAB catalyzed the time-dependent decrease of succinyl-CoA and benzoyl-CoA with a simultaneous increase of a new compound, which comigrated with benzoylsuccinyl-CoA obtained in another study (Fig. 2C) [10]. The chemical nature of this product as a ketone-containing compound was further supported by converting it to a hydrazone by adding phenylhydrazine, resulting in a shift of the retention time (Fig.…”
Section: Functional and Molecular Properties Of Bbsabsupporting
confidence: 67%
“…BbsAB is expected to turn over ( S )‐2‐benzoylsuccinyl‐CoA as substrate, because this diastereomer was found to be produced by BbsCD, the enzyme preceding BbsAB in the pathway (Fig. 1) [10]. Therefore, ( S )‐2‐benzoylsuccinyl‐CoA was modelled based on the geometric/electrostatic properties of the active site of BbsAB thereby starting from the firmly bound CoA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations